Penerapan Metode Webqual 4.0 dan IPA Dalam Mengukur Kualitas Website VISLOG PT. Citra Surya Indonesia - Lilyani Asri Utami; Abdul Gani; Suparni Suparni (Komputika : Jurnal Sistem Komputer, 2020)
The role of the website is very important in all fields, especially for organizations or companies. Since 2017, evaluation of the VISLOG website owned by PT. Citra Surya Indonesia has never been done, so it does not know the quality of the website for its users. The purpose of this study is to measure the current level of website quality based on user ratings of actual perceived quality and expected ideal quality. This research is a quantitative descriptive study with dimension webqual 4.0 approach which is assessed based on the perspective of the level of performance and importance using the Importance Performance Analysis (IPA) method. User data is obtained by distributing questionnaires based on 3 dimensions on webqual 4.0, namely usability, information and service interaction dimensions. Obtained analysis results show that the VISLOG website is in accordance with user expectations with the results of the analysis of conformity of 101.19% or >100% and the average gap analysis result (GAP) of 0.05 or >0. IPA results shows quadrant III and quadrant IV, both quadrants have a low level of performance that will affect the level of importance or expectations of users.